2012
DOI: 10.1002/dc.22903
|View full text |Cite
|
Sign up to set email alerts
|

Increased diagnostic yield of endoscopic ultrasound‐guided fine needle aspirates with flow cytometry and immunohistochemistry

Abstract: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) is the most sensitive and specific test for establishing a tissue diagnosis for many gastrointestinal malignancies; however, cytologic morphology alone may not be definitive for subsets of tumors. Our aim was to quantify the impact of the broad application of flow cytometry (FC) and immunohistochemistry (IHC) on EUS-FNA diagnostic yield. A retrospective chart review was performed on EUS procedures at a tertiary referral, academic medical center. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…[11][12][13] Difficult differential diagnoses such as SPN from pancreatic neuroendocrine neoplasms are one of the main reasons to obtain an adequate cell block at the time of EUS-FNA so that immunohistochemistry may be performed to elucidate the correct diagnosis, which has been published previously. 14 15 Among all FNA samples tested, E-cadherin, b-catenin, and CD10 demonstrated the greatest difference between pancreatic endocrine neoplasms and SPN. It is interesting to note that the patterns of E-cadherin and b-catenin staining were highly specific for this distinction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[11][12][13] Difficult differential diagnoses such as SPN from pancreatic neuroendocrine neoplasms are one of the main reasons to obtain an adequate cell block at the time of EUS-FNA so that immunohistochemistry may be performed to elucidate the correct diagnosis, which has been published previously. 14 15 Among all FNA samples tested, E-cadherin, b-catenin, and CD10 demonstrated the greatest difference between pancreatic endocrine neoplasms and SPN. It is interesting to note that the patterns of E-cadherin and b-catenin staining were highly specific for this distinction.…”
Section: Discussionmentioning
confidence: 96%
“…They did not demonstrate the classic features of SPN as described previously, such as pseudopapillae, capillary cores with metachromatic myxoid material, coffee bean/grooved nuclei, clear vacuoles in the cytoplasm, slender cytoplasmic processes, or hyaline globules . Difficult differential diagnoses such as SPN from pancreatic neuroendocrine neoplasms are one of the main reasons to obtain an adequate cell block at the time of EUS‐FNA so that immunohistochemistry may be performed to elucidate the correct diagnosis, which has been published previously . In 2009, Burford et al eloquently outlined which immunohistochemical stains could best distinguish pancreatic neuroendocrine neoplasms from SPN .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that multiparameter FC has a sensitivity higher than cytomorphology in detecting leptomeningeal disease in aggressive B-NHL in CSF samples (Hegde et al, 2005;Quijano et al, 2009;Stacchini et al, 2012a). In EUS-FNA, considered the procedure of choice for diagnosing and staging various gastrointestinal and mediastinal malignancies in locations that may be hard to access by other methods, FC has been successfully applied to detect lymphomas (Mehra et al, 2005;Ribeiro et al, 2010;Stacchini et al, 2012b;Sodikoff et al, 2013). In EUS-FNA, considered the procedure of choice for diagnosing and staging various gastrointestinal and mediastinal malignancies in locations that may be hard to access by other methods, FC has been successfully applied to detect lymphomas (Mehra et al, 2005;Ribeiro et al, 2010;Stacchini et al, 2012b;Sodikoff et al, 2013).…”
Section: Background Informationmentioning
confidence: 99%
“…In OF specimens, FC has been recently utilized to detect reactive T cell infiltrate in uveitis and to diagnose intraocular lymphomas (Sen et al., ; Davis et al., ; Missotten et al., ). In EUS‐FNA, considered the procedure of choice for diagnosing and staging various gastrointestinal and mediastinal malignancies in locations that may be hard to access by other methods, FC has been successfully applied to detect lymphomas (Mehra et al., ; Ribeiro et al., ; Stacchini et al., ; Sodikoff et al., ).…”
Section: Commentarymentioning
confidence: 99%
“…Anyway, targeting of lesions in the distal duodenum may be easier by using the 25-G needle due to less friction and easier penetration 77. Another recent study demonstrated that with an adequate tissue sample, broad application of cytometry and immunohistochemistry increased the diagnostic yield of EUS-FNA 78. Recently, EUS-FNA biopsy can be performed with a new 19-G histology needle, being feasible for histopathology diagnosis of intraintestinal and extraintestinal mass lesions, offering the possibility of obtaining a core sample for histological evaluation in the majority of cases, with an overall diagnostic accuracy of over 85% 79…”
Section: From the Pastmentioning
confidence: 99%